Pengaruh Media Tangram Berbasis Teori Didaktik Situasional Terhadap Hasil Belajar Kelas IV SD Materi Komposisi dan Dekomposisi Bangun Datar - Mawaddah, Alfiani; Kamilah, Intan Putri; Wijayanti, Putri Tri; Putra, Zetra Hainul; Oktaviani, Cici (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2025)
This study aims to determine the effect of using tangram media based on the Situational Didactic Theory (TDS) on students’ learning outcomes in the topic of composition and decomposition of plane figures in fourth-grade elementary school. The research employed a quasi-experimental design consisting of two groups: an experimental class that used tangram media integrated with TDS and a control class that received conventional instruction. Data were collected through pre-test and post-test assessments and analyzed using normality tests, homogeneity tests, and an independent sample t-test. Findings revealed that all data were normally distributed and homogeneous, meeting the assumptions for parametric analysis. The t-test result showed a significance value of 0.006, indicating a significant difference in learning outcomes between the two groups. Students in the experimental class demonstrated higher learning gains, confirming that tangram media based on TDS effectively enhances geometric understanding. Therefore, this approach is recommended as an alternative instructional strategy for teaching mathematics in elementary schools.